Acarofauna asociada al mantillo de un bosque esclerófilo del Parque Nacional La Campana (Chile) - Salazar Martínez, Ana Ernestina (1996)
Acari from a sclerophyllous shrubland in the V Region (Chile) were obtained from litter sampling units through Berlese funnels. Species composition, diversity, and temporal variation during three years were analyzed. Oribatida and Uropodina (Gamasida) were recorded as principal saprophagous. Predators were represented by Actinedida. Both species composition and diversity differed during the annual cycle. Two groups were defined: «xerophyllous», present when the peack of litter fall was produced, and «higrophyllous», associated to the time of highest moisture.